The Colour of Eco-Crime - Bertenthal, Alyse (The British journal of criminology, 2023)
In taking up the mantle of ‘green,’ criminologists concerned with environmental harm have succeeded in shifting criminology away from its anthropocentric focus on crime and harms committed to and by humans. While this framework has generated a large body of scholarship, it has also occluded important discussions about the significance of race and racial ideologies in the ongoing construction of crime, even—and especially—when depictions of crime do not explicitly reference humans. This article employs semiotic analysis of media images of eco-crime to demonstrate that the ways in which we see eco-crime—like ways of seeing crime more generally—construct images of race and contribute to the establishment of racialized relations. By placing eco-crime in a visual context and deconstructing the implicit and explicit racial imagery of eco-crime, I prompt criminologists to consider more critically issues of race and racialization in green criminology.